2018
DOI: 10.1152/ajprenal.00409.2017
|View full text |Cite
|
Sign up to set email alerts
|

Glucose dilates renal afferent arterioles via glucose transporter-1

Abstract: Glomerular hyperfiltration occurs during the early stage of diabetes. An acute glucose infusion increases glomerular filtration rate. The involvement of tubuloglomerular feedback response and direct effect of glucose on the afferent arterioles (Af-Arts) have been suggested. However, the signaling pathways to trigger Af-Art dilatation have not been fully identified. Therefore, in the present study we tested our hypothesis that an increase in glucose concentration enhances endothelial nitric oxide synthesis acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…We recently demonstrated that an increase in luminal glucose concentration dilates the mouse Af-Art by stimulation of the endothelium-derived NO production via GLUT1. 76 Another study by Toma et al 77 also showed that high glucose in vascular perfusate rather than bath solution dilates the rabbit Af-Art, which involves the local accumulation of succinate and activation of G protein-coupled metabolic receptor GPR91. Additionally, acute hyperglycemia stimulates b-cells to produce and secret insulin.…”
Section: Glucose-induced Hyperfiltration Is Mediated By Macula Densa mentioning
confidence: 99%
“…We recently demonstrated that an increase in luminal glucose concentration dilates the mouse Af-Art by stimulation of the endothelium-derived NO production via GLUT1. 76 Another study by Toma et al 77 also showed that high glucose in vascular perfusate rather than bath solution dilates the rabbit Af-Art, which involves the local accumulation of succinate and activation of G protein-coupled metabolic receptor GPR91. Additionally, acute hyperglycemia stimulates b-cells to produce and secret insulin.…”
Section: Glucose-induced Hyperfiltration Is Mediated By Macula Densa mentioning
confidence: 99%
“…Zhang et al. used the selective GLUT1 antagonist and NOS inhibitor, respectively, to block the response of the vascular and afferent arterioles to hyperglycemia successively; it indicated that vasodilation induced by hyperglycemia is achieved through the GLUT1-mediated endothelium-dependent production of NO ( 97 ).…”
Section: Tubular Mechanisms For Hyperfiltration In Early Diabetic Kid...mentioning
confidence: 99%
“…A rapid glucose-induced dilation has already been observed in mouse AA. 6 Here, we showed that hyperglycemia-induced dilation is weaker in EA than AA suggesting increased filtration pressure leading to hyperfiltration. Acute hyperglycemia did indeed increase GFR in mice, an effect that could be blocked by GsMTx4.…”
Section: Discussionmentioning
confidence: 61%
“…NO production in isolated AA and HUVECs was measured using the cell-permeable fluorescent NO indicators 4,5-diaminofluorescein diacetate and 3-amino, 4-aminomethyl-2′,7′-difluorofluorescein diacetate, respectively, as described previously. 6…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation